Implementasi Aplikasi Isi Rapor di SMA Darussa’adah Glumpang Tiga Kabupaten Pidie - Syibran Malasyi; Sufandi Iswanto; Heri Fajri (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2020)
This study aims to determine the implementation process of the Report Card Content Application in Darussaʻadah Glumpang Tiga Private High School, the components contained in the Report Card Content Application and the advantages and constraints of using the Report Card Content Application at Darussaʻadah Glumpang Tiga Private High School. This study used a qualitative research method with a descriptive approach, while data collection was carried out in three ways, namely interviews, documentation, and observation. The population of this study is the principal, administrative staff, and teachers of SMA Swasata Darussaʻadah Glumpang Tiga, totaling 57 people, and the sample that the author has determined is the principal, 1 teacher who teaches the field of History, 1 teacher. who teaches PAI, 1 teacher who teaches Arabic, and 2 administrative employees, namely the head of administration and the deputy head of Administration. The results showed that the implementation of the Report Card Content Application in Darussaʻadah Glumpang Tiga Private High School at the beginning of its application was very good and very helpful for teachers, but obstacles and problems were also unavoidable, which was proven by some teachers who had difficulty using this Report Card Application. The obstacles that occur are dominated by elderly teachers who still have very little knowledge of technology. The components or features available in the Report Card Content Application are very complete and in accordance with the various criteria for teacher assessment of students.